Preparation and Characterization of High Surface Area Nanosilica from Iraqi Sand via Sol-Gel Technique - Mahmood, Firdews Sh.; Hussein, Hussein Q.; Abdulwahhab, Zeinab T. (Journal of Petroleum Research and Studies, 2022)
The present study revealed a low-cost process for utilizing desert sand for preparing nanosilica by sol-gel technique. This work required sodium hydroxide, concentrated hydrochloric acid, distillate water as raw materials, and Iraqi sand. Nanosilica sample was characterized by X-Ray Diffraction (XRD), scanning electron microscopy analysis (SEM), atomic force microscope(AFM), surface area (BET) method, and fourier transform infrared (FTIR). The XRD result of produced sample is referred to as amorphous silica, and it has a broad peak at 2Θ= 22° – 22.5 º. SEM showed spherical, agglomerated silica particles with a diameter range of 26.57–28.93 nm. In addition, the average particle size was 76.35nm, with a dimension range of 40-110 nm, and the surface area was 510.96 m²/g. The inclusion of hydrogen-bonded silanol groups (Si–O–H) at 3437.15 cm-¹ and siloxane groups (Si–O–Si) at 1087.85 cm-¹in the FTIR spectra.